Temporal trends of the water quality of tributaries of the São Francisco River between Três Marias and Pirapora - MG (Research, Society and Development, 2022)
Water is an essential natural resource for cell metabolism and the development of human society. Its availability, however, has been affected by the pollution to which it is subjected. In this question, there is the São Francisco watershed, which, although it has a unique economic and cultural role for the population of the semi-arid region, suffers the weight of anthropization, since it is exploited by agricultural activities and to drain urban and industrial effluents. To tell this, it is important to monitor the quality of its water and its tributaries, in order to implement an efficient management of this asset. That said, this research aims to evaluate the temporal trend of the behavior of the physicochemical attributes of water quality, between 2017 and 2021, in the stretch of the São Francisco river in Três Marias and in the tributaries Rio Abaeté, Formoso and De Janeiro. The data used for the analysis were produced by the Scientific Expedition Amigos das Águas and collected from the portal of the Water Supply and Sewage Service of Pirapora SAAE - MG. For statistical analysis, Sisvar was used, and the parameters evaluated were: aluminum, apparent color, iron, phosphate, nitrate, nitrite, sedimentable solids, suspended solids and pH, in accordance with CONAMA n° 357/2005. The criteria evaluated are within the established limits. However, it is recommended to include the criterion of thermotolerant coliforms, in order to better ensure the viability of the water resource.